Student-centred approaches to Russian language teaching : insights, strategies, and adaptations - Nuss, Svetlana V.; Martin, Cynthia L. (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Student-Centred Approaches to Russian Language Teaching looks at how the field of Russian language pedagogy has evolved in recent years due to advances in technology along with shifts in attitudes to language pedagogy, and how the pandemic has compounded and accelerated these changes. This edited collection brings together different perspectives from the field of Russian language pedagogy. With pedagogical conversations now centered around students and their needs, as well as the evolving role of the teacher in the 21st century, this volume highlights the diverse ways in which instructional practices have evolved, making curriculum and assessment more student-centered and Russian language learning more engaging. The collection will be of interest to current and future instructors of Russian as a foreign or additional language who wish to diversify their instruction, as well as students of Russian language pedagogy and second language learning and teaching"--
Keywords: Russian language -- Study and teaching -- Foreign speakers; Student-centered learning; FOREIGN LANGUAGE STUDY / General; FOREIGN LANGUAGE STUDY / Russian